Pemikiran Karl Marx Tentang Dialektika - Imam Wahyuddin (TASAMUH: Jurnal Studi Islam, 2016)
When Karl Marx was in Paris, Marx began to examine two issues that it raises concrete questions that are not discussed by the socialists. The first problem, why was the French revolution failed? Why did Europe become more away from freedom compared to the period before the revolution? The second problem, what is the significance of a new industrial revolution, great revolution technology in factories, mines, and transportation transform economic life, social and political world which brings with him a wealth for a few people and spreading poverty and alienation for others. To answer these problems in their daily Marx lot of reading and thinking and to learn from the socialists. Socio-economic conditions as well as human culture around the life of Marx are paying attention, where the workers who work not based on the ground of duress. The work was merely a means to satisfy the needs of capitalists manipulate workers to gain Marx’s view that capitalist society is always oppressive humans can only be changed with the revolutionary approach. The spirit of Karl Marx is full concentration on economic science imagination resulting in a new insight and brought back to the philosophy of Hegel. In a text entitled “critique of Hegel’s dialectic and philosophy as a unified” look a philosophy of economic life and interpretation of economic history. Historical materialism and dialectical materialism is the logic of the methodological principles and epistemologies of historical materialism, the philosophy of just criticizing the concepts of historical materialism from a political angle to give the boundary between science and ideological concepts that accompany the new science.